Severe Mental Illness Diagnoses and Their Association With Reoffending in a Sample of Men Adjudicated for Sexual Offences - Aelick, Charlotte A.; Babchishin, Kelly M.; Harris, Andrew J. R. (Sexual Offending: Theory, Research, and Prevention, 2020)
The current study examined the relationship between mental illness and recidivism in a sample of 409 men adjudicated for sexual offences who scored higher than average on an established risk assessment tool (Static-99R). Participants were from all provincial correctional systems (except Prince Edward Island) and all regions of the Correctional Service of Canada. Severe mental illness diagnoses, with the exception of some personality disorders, were not associated with recidivism (after an average follow-up of 11 years). While some personality diagnoses were initially related to recidivism, this relationship often disappeared or was attenuated after controlling for substance misuse and risk score on the Static-99R. There were two exceptions: Histrionic and narcissistic personality disorders continued to predict sexual recidivism after controlling for Static-99R and substance misuse history. In sum, the current study suggests that severe mental illness diagnoses are not associated with higher rates of recidivism after accounting for risk score and substance misuse in men with sexual offences, with the exception of histrionic and narcissistic personality disorder diagnoses. For this reason, risk judgements that weigh both known risk factors and severe mental illness may overestimate an individual’s risk to reoffend.